Children in care or in need: educational progress at home and in care. (4th July 2019) - Sinclair, Ian; Luke, Nikki; Berridge, David
ABSTRACT: By age 16 the attainment of most children in or on the edge of out of home care has fallen well behind the average for their age. This paper uses the English National Pupil Database to examine how much of this falling behind occurs before the age of seven, and how any subsequent decline relates to time in care as against time outside it. We compare the previous progress of three groups of 16-year-olds: 5175 looked after by the state (CLA), 17, 392 in need but not in care (CIN), and 22, 567 children matched with the CLA or CIN on initial attainment, special educational needs, and eligibility for free school meals. We found that the attainment of the CIN and those CLA not yet in care was around one standard deviation below the cohort average at age seven. It then fell relative to their peers while their rate of unauthorised absences and exclusions grew. Removal from home to care appeared to halt or greatly reduce this decline but did not, on average, reverse it. We conclude that educational interventions for CLA should also include CIN, start before seven, target both school and family, and exploit the educational opportunity which care provides.